THE SECTORAL CONSTITUTIONAL PRINCIPLES AND CRIMINAL LAW: A JURISPRUDENTIAL STUDY - Moreira da Veiga Pessoa , Bruno (Revista Gênero e Interdisciplinaridade, 2023)
The work on screen discusses the constitutional principles, with regard specifically to sectoral constitutional principles, in view of the need to delimit the study. The aim was to achieve the application of constitutional principles in the scope of Criminal Law, analyzing some judgments in order to understand the jurisprudential position regarding them.